White blood cell segmentation for acute leukemia bone marrow images - Lim, Huey Nee; Mohd Yusoff, Mashor, Prof. Madya. Dr.; Rosline, Hassan, Dr. (Institute of Electrical and Electronics Engineers (IEEE), 2012)
Link to publisher's homepage at http://ieeexplore.ieee.org/